O sistema produto serviço centrado em personagens como fonte de estímulo às habilidades sociais na infância - Cutin, Bruno Albornoz (Universidade do Vale do Rio dos Sinos, 2016)
This paper aims to expand knowledge related to the development of social skills in childhood, especially on what is in the capabilities of the design. In order to assist professionals in this area to develop projects with greater ownership of the issue, we sought to understand how is the process of designing characters that encourage the development of Social Skills (SS) and how to design a PSS these characters, in which all elements assist in the SS development. It has been researched all issues considered important for the development of design activity / workshop (Strategic Design and Product System and Service / Character: Design and Construction / Toys, Character and Social Skills). The workshop was held with professionals in the areas of: design, psychology and communication. The activities were designed, coordinated and evaluated by a board. At the end it was developed two characters (Golf and Ploft) with their SPS.
Keywords: Design; Personagem; Habilidades Sociais (HS); Sistema Produto Serviço (SPS); Design; Character; Social Skills (SS); Product Service System (PSS); ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial